The implementation of the United Nations Convention to combat desertification in four of the Sahel states : Burkina Faso, Mali, Niger and Sénégal - (:unkn) unknown (My University, 2024)
Environmental law in West Africa can be considered a crossroads of international treaty law, traditional customary law, and colonial law. This thesis employs institutional analysis and comparative law to assess the legal frameworks for land protection in the context of implementing the United Nations Convention to Combat Desertification (UNCCD) in four Sahelian States, namely Burkina Faso, Mali, Niger, and Senegal. The analysis reveals that environmental law is a work in progress, and the corpus of legislation is fragmented and incomplete. The law lacks integration of fundamental concepts such as ecological damage, common goods, local conventions, and land grabbing, which limit its effectiveness in Africa and prevent it from safeguarding land from various forms of degradation, including land grabbing. Capacity building of key stakeholders and drafting of sub-regional regulation for land protection in the UEMOA sub-region are recommended as potential solutions. A sub-regional community-level regulation could address institutional and legal weaknesses in the countries' internal systems
Keywords: African Research